2012
DOI: 10.1186/1742-2094-9-12
|View full text |Cite
|
Sign up to set email alerts
|

Japanese encephalitis virus induces matrix metalloproteinase-9 expression via a ROS/c-Src/PDGFR/PI3K/Akt/MAPKs-dependent AP-1 pathway in rat brain astrocytes

Abstract: BackgroundJapanese encephalitis virus (JEV) infection is a major cause of acute encephalopathy in children, which destroys central nervous system (CNS) cells, including astrocytes and neurons. Matrix metalloproteinase (MMP)-9 has been shown to degrade components of the basal lamina, leading to disruption of the blood-brain barrier (BBB) and to contribute to neuroinflammatory responses in many neurological diseases. However, the detailed mechanisms of JEV-induced MMP-9 expression in rat brain astrocytes (RBA-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
80
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 48 publications
(82 reference statements)
10
80
1
Order By: Relevance
“…5, E and G). NADPH oxidase/ROS generation has been shown to initiate EGFR or PDGFR activation in various cell types (17,31). Here, we showed that pretreatment with Edaravone, APO, or DPI or transfection with Nox2 or Nox4 siRNA markedly reduced LPS-stimulated EGFR and PDGFR phosphorylation in HPAEpiCs (Fig.…”
Section: Involvement Of Nadph Oxidase and Ros Generation In Lps-inducmentioning
confidence: 54%
See 1 more Smart Citation
“…5, E and G). NADPH oxidase/ROS generation has been shown to initiate EGFR or PDGFR activation in various cell types (17,31). Here, we showed that pretreatment with Edaravone, APO, or DPI or transfection with Nox2 or Nox4 siRNA markedly reduced LPS-stimulated EGFR and PDGFR phosphorylation in HPAEpiCs (Fig.…”
Section: Involvement Of Nadph Oxidase and Ros Generation In Lps-inducmentioning
confidence: 54%
“…It has been reported that several G protein-coupled receptors initiate the PI3K/Akt pathway through transactivation of the EGFR or PDGFR in various cell types (3,16,31). However, little was known about the mechanisms of LPS that initiate the expression of ICAM-1 mediated through c-Src-dependent transactivation of EGFR or PDGFR in HPAEpiCs.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs, a large family of calcium‐dependent zinc‐containing endopeptidases excreted as zymogens by a variety of cells including fibroblasts, macrophages, and neutrophils, play a critical role in tissue remodeling and degradation of extracellular matrix components 26. Previous studies have shown that MMP9 was closely correlated with inflammation, including Helicobacter pylori‐associated gastritis and encephalitis virus 27, 28. NM23, a metastasis suppressor protein, is associated with tumor metastasis, while its expression and prognostic value in GC is still controversial 29.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, the kinetics of virus-induced survival signaling varies among cell lines and flaviviruses, and as a consequence, the extent of apoptosis is affected. With regard to WNV, Scherbik and Brinton (28) reported that infection of MEFs significantly increases phospho-Akt within 2 h of infection and this effect is sustained for more than 24 h. Similarly, JEV infection of RBA-1 cells activates the PI3K/Akt pathway, resulting in stimulatory phosphorylation of Akt within minutes (49). In contrast, WNV infection of neuro2A cells, a mouse neuroblastoma cell line, results in extensive cell death in less than 72 h, even at very low MOIs (50).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, several publications have shown that depending upon the specific flavivirus and cell type involved, PI3K/Akt signaling is activated within minutes (or hours) of infection with WNV, DENV, and JEV (26,27,49). Moreover, caspase-3 activation does not occur until later in infection, after the activation of PI3K/Akt has subsided.…”
Section: Discussionmentioning
confidence: 99%